Investigating the hydration status, metabolic responses and cognitive-motor performance in cyclists under heat stress - Herculano, E. A.; Sousa Filho, L. F.; de Almeida, R. D.; Franca, T. C. L.; de Oliveira, N. M.; Camerino, S. R. A. S.; Lima, R. C. P.; Prado, E. S. (Revista Brasileira de Ciência e Movimento, 2019)
The aim of this study was to evaluate the hydration status, metabolic responses and cognitive-motor performance during a combined cycling race in the heat. The combined cycling race (such as a simulated cycling race), consisted of 67 km under heat stress conditions. Before and after cycling race, ten male cyclists (30.5 ± 4.9 years) were evaluated for hydration status, biochemical and hematological parameters and cognitive-motor performance. Blood samples were collected for biochemical and hematological analysis. The hydration status was assessed by evaluating a change in body mass percentage loss (% BM), urinary color, specific gravity and blood parameters. To evaluate cognitive-motor performance, we measured immediate memory, motor coordination and reaction time. Environmental conditions during exercise were an average of 27.1 ± 0.7 °C for Wet-Bulb Globe Temperature (WBGT) Index. The hydration status (% BM: - 3.26 ± 0.57), demonstrated that the cyclists were dehydrated after race. We found an increase in the concentrations of ammonia (%: 74.94 ± 18.64) and its metabolites (urea and urate) after the race. The concentrations of blood glucose and lactate were not significantly different after the race. Exercise promoted a significant increase in enzyme biomarkers for muscle damage. Red blood cells counts were unchanged. However, leukocyte count (%: 178.55 ± 28.64) increased significantly. No changes were observed in the cognitive-motor tasks. Under these conditions, the results of the present study indicate that dehydration and/or hyperammonemia does not negatively affect cognitive-motor performance in acclimated cyclists.